Analisis Gaya Bahasa pada Berita Politik CNN Indonesia edisi Juli 2024 serta Pemanfaatannya pada pembelajaran Bahasa Indonesia di SMA - Beladiantika, Elsa Eges (Universitas Mathla'ul Anwar Banten, 2025)
Analysis of Language Style in CNN Political News July-August 2024 Edition and Its Use in Learning Indonesian in High School. Indonesian and Regional Language and Literature Education Study Program, Undergraduate Program (S1) Faculty of Teacher Training and Education, Mathla'ul Anwar University, Banten. This research aims to analyze the language style used in the July-August 2024 edition of CNN's political news and explore its use in learning Indonesian at the high school level. Language style refers to the choice of words used by the writer or author. Through a descriptive qualitative analysis method of political news, this research identifies language styles, such as figures of speech; comparison, contradiction, assertion and satire applied to political news. The total data that the author obtained from July-August was 1,247 data. Based on July, hyperbole 80 data, personification not found, metaphor 22 data, litotes 21 data, antithesis 3 data, pleonasm 1 data, repetition 12 data, irony 1 data, cynicism not found. Then in August, hyperbole 418 data, personification 176 data, metaphor 265 data, litotes 111 data, antithesis 34 data, pleonasm 17 data, repetition 55 data, irony 27 data, cynicism 1 data. This researcher also examines how political news text material as a learning resource is used to increase students' motivation and ability to speak Indonesian.